Base‐Assisted C−H Bond Cleavage in Cross‐Coupling: Recent Insights into Mechanism, Speciation, and Cooperativity. Issue 3 (13th December 2019) - Carrow, Brad P.; Sampson, Jessica; Wang, Long
Abstract: This review analyzes recent mechanistic studies that have provided new insights into how the structure of a metal complex influences the rate and selectivity of base‐assisted C−H cleavage. Partitioning a broader mechanistic continuum into classes delimited by the polarization between catalyst and substrate during C−H cleavage is postulated as a method to identify catalysts favoring electrophilic or nucleophilic reactivity patterns, which may be predictive based on structural features of the metal complex (i. e., oxidation state, d‐electron count, charge). Multi‐metallic cooperativity and polynuclear speciation also provide new avenues to affect energy barriers for C−H cleavage and site selectivity beyond the limitations of single metal catalysts. An improved understanding of mechanistic nuances and structure‐activity relationships on this important bond activation step carries important implications for efficiency and controllable site selectivity in non‐directed C−H functionalization. Abstract :